Strong interfacial modified aramid fabric reinforced degradable thermosetting composites: reinforcing and tribological effects. (June 2022) - Yang, Y.; Min, C.; Xu, Z.; Liang, H.; Li, Q.; Ji, M.; Liu, S.; Wang, W.; Li, N.; Pei, X.
Abstract: In this work, dense molybdenum disulfide (MoS2 ) nanosheets were grown onto polydopamine (PDA) functionalized aramid fabric (AF) surface via a simple hydrothermal method to improve the wettability between AF surface and polyhexahydrotriazine (PHT) resin, thus resulting in stronger AF/resin interfacial bonding. The PDA-assisted surface modification on AF generated a high active interface allowing the nucleation and subsequent growth of MoS2 . Moreover, this nanosheet-coated reinforcement fiber enabled the viscous liquid of resin precursor to spread over and form intimate contact with its surface, which eventually promoted the formation of strong interfacial bonding between AF-MoS2 and cured resin matrix. In addition, the enhanced interfacial bonding between the reinforcement and matrix generated stable mechanical interlock within the resulting AF-MoS2 /PHT composites, and thus, contributed better thermal stability, higher tensile strength, and tribological properties. Compared with AF/PHT composites, the tensile strength and elongation at break of the AF-MoS2 /PHT composites increased by 32.5% and 50%, and the average friction coefficient and wear rate of AF-MoS2 /PHT composites decreased by 43.9% and 86.3%, respectively. Furthermore, the composites realized the non-destructive recovery of expensive AF at 25 °C. Overall, our study demonstrates a dependable strategy to construct the recyclable AF-MoS2 /PHT composites, which exhibit valuable applications in tribology. Graphical abstract: Image 1 Highlights: The AF-MoS2 was fabricated via a simple hydrothermal method to strengthen the interfacial bonding with PHT resin after curing with enhanced performance. Compared with AF/PHT, the tensile strength and elongation at break of the AF-MoS2 /PHT composites increased by 32.5% and 50%. The average friction coefficient and wear rate of AF-MoS2 /PHT composites decreased by 43.9% and 86.3% as compared to AF/PHT composites. The prepared AF-MoS2 /PHT composites can be degraded, thereby realizing non-destructive recycling of expensive AF and the recovery of 78.2% monomer TPE-Q.